Native and endemic Iranian Nepeta spp.: powerful antimicrobial agents: Native and endemic Iranian Nepeta spp - Hadi, Najmeh; Nikolić, Miloš; Sefidkon, Fatemeh; Shojaeiyan, Abdolali; Šiler, Branislav; Mišić, Danijela; Yahyazadeh, Mahdi (Cellular and Molecular Biology, 2023)
Pathogenic microorganisms are more or less successfully treated by synthetic chemical compounds, whose residues often cause serious health problems. Plant specialized metabolites with antimicrobial properties have for a long time been the focus of both medicine and pharmacology. This study was conducted to evaluate the in vitro antimicrobial activity of methanol extracts of selected endemic and native Iranian Nepeta species against some of the most important pathogenic bacteria and fungi. The results indicated that N. kotschyi leaf extract was the most efficient against the tested bacteria, with Pseudomonas aeruginosa being the most sensitive and fungal species were more susceptible to the extracts than bacterial strains. Nepeta spp. extracts showed a strong antifungal activity against micromycetes, except for quite resistant Aspergillus niger. Antibacterial MIC values (mg.mL-1) ranged from 0.01 (N. kotschyi) to 0.20 (N. crassifolia), while antifungal MIC values ranged from 0.02 (N. crassifolia, N. kotschyi, N. menthoides, and N. cataria) to 0.13 (N. crassifolia and N. menthoides). When compared to positive controls, in most cases the extracts performed much better. The recorded antimicrobial activity candidates the selected 4 endemic and native Iranian Nepeta spp. as prospective and promising antimicrobial agents to be used in both pharmacology and biotechnology.